Risk Factors for Development of Rectal Neuroendocrine Tumors Longer Than 9 mm: Retrospective Cohort - Lima de Castro, Juliana Silveira; Vieira da Rocha, Evandra Cristina; do Vale, Vanessa Assis; Mendonça, Paula; Marques Jr., Oswaldo Wiliam; Taglieri, Eloy; Correa Koyama, Francisco Susumu; Cardoso Filho, Celso Augusto Milani; Nakagawa, Wilson Toshihiko (Turkish Journal of Gastroenterology, 2021)
Background: Rectal neuroendocrine tumors (R-NET) represent the most frequent of gastroenteropancreatic neuroendocrine neoplasms(NEN-GEP) according to the United States Surveillance, Epidemiology, and End Results database. With an annual percentage of occurrenceincreasing to 8.2% of all rectal neoplasms, R-NET affect less than 2% and are reported in only 0.05% to 0.07% of patients undergoingcolorectal cancer (CRC) screening. The primary objective of this study was to assess the risk factors associated with R-NET greaterthan 10 mm. As a secondary objective, it was also aimed to evaluate the response to endoscopic treatment.Methods: This was a retrospective study, using data collected through the analysis of medical records of colonoscopies performed fromJanuary 2008 to December 2014. Records of polypectomies were identified, and the results were searched for pathological findings ofR-NET. We also gathered epidemiological data and outcomes as risk factors for lesions greater than or equal to 10 mm, with local anddistant recurrence.Results: During the study period, 18 218 colonoscopies were performed and 10 865 polypoid lesions were detected and removed, 20 withR-NET anatomopathology. The detection rate was 0.1%. The risk factors associated with major lesions were Japanese ethnicity, the lackof previous cancer diagnosis, and a Ki67 index > 2%. The mean follow-up was 56.6 months, and there was no local lymph node recurrenceor distant relapse.Conclusion: This study concludes that endoscopic resection is a good and effective method for treatment of Grade 1 rectal NET smallerthan 11 mm, with high cure rates and low rates of local or distant relapse.